Historical development and current status of emergency nursing in Turkey - (:unkn) unknown (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2009)
As the demand for high quality Accident and Emergency Departments and nursing staff increases throughout Turkey, the need for more specialized emergency nurse training has also increased. Although there have been a number of positive developments regarding emergency nursing standards, the general quality of emergency nurse training needs to be improved and job definitions amended to better reflect the specialist duties of emergency nurses.
Keywords: Emergency nursing; historical development